# How may I align the following set of equations as represented in the image?

If IEEEeqnarray environment is not best-suited for this particular alignment, what could be the best environment to be used?

\documentclass[11pt,a4paper]{article}
\usepackage{blindtext}
\usepackage{mathtools}
\usepackage{IEEEtrantools}
\begin{document}
\begin{IEEEeqnarray*}{rCl}
(x-a)(x-2a)(x-3a)(x-4a)=x^{4}-P_{1}x^{3}+P_{2}x^{2}-P_{3}x+P_{4}.\\
\shortintertext{Here}
P_{1}&=&a+2a+3a+4a=10a,\\
P_{2}&=&1\times 2a^{2}+1\times 3a^{2}+1\times 4a^{2}+2\times 4a^{2}+3\times 4a^{2}=35a^{2},\\
P_{3}&=&2\times 3\times 4a^{3}+1\times 3\times 4a^{2}+1\times 2\times 4a^{3}+1\times 2\times 3a^{3}=50a^{3},\\
P_{4}&=&1\times 2\times 3\times 4a^{4}=24a^{4}.
\shortintertext{so that}
(x-a)(x-2a)(x-3a)(x-4a)=x^{4}-10ax^{3}+35a^{2}x^{2}-50a^{3}x+24a^{4}.
\end{IEEEeqnarray*}
\end{document}


The presentation of your alignment is not really that accurate. So, I assume the following will be sufficient:

\documentclass{article}
\usepackage{array}
\begin{document}
$(x - a)(x - 2a)(x - 3a)(x - 4a) = x^4 - P_1 x^3 + P_2 x^2 - P_3 x + P_4.$
Here
$\renewcommand{\arraystretch}{1.3} \begin{array}{r@{}>{{}}l@{}r@{}>{{}}l} P_1 &= a+2a+3a+4a &&= 10a, \\ P_2 & \multicolumn{3}{@{}l}{{}= 1 \times 2a^2 + 1 \times 3a^2 + 1 \times 4a^2 + 2 \times 4a^2 + 3 \times 4a^2} \\ &&&= 35a^2,\\ P_3 & \multicolumn{3}{@{}l}{{}= 2 \times 3 \times 4a^3 + 1 \times 3 \times 4a^2 + 1 \times 2\times 4a^3 + 1 \times 2 \times 3a^3} \\ &&&= 50a^3,\\ P_4 &= 1 \times 2 \times 3 \times 4a^4 &&= 24a^4, \\ \end{array}$
so that
$(x - a)(x - 2a)(x - 3a)(x - 4a) = x^4 - 10ax^3 + 35a^2 x^{2} - 50a^3 x + 24a^4.$
\end{document}


Multiple alignments that's not strictly adhered to (some lines use the alignment points and some don't) is difficult to do with standard align and friends. Using an array may circumvent this difficulty with the aid of \multicolumn.

The use of the array package above is not really needed, but I've used it anyway.

• This is the exact alignment I wanted to have. I apologise for the inconvenience I caused by not making my set up inaccurate. Thank you very much for dedicating your precious time in looking to this matter. Dec 9, 2014 at 20:17

Why not this simple way?

\documentclass{article}

\usepackage{mathtools}

\begin{document}

\noindent We have
\begin{align*}
\MoveEqLeft (x - a)(x - 2a)(x - 3a)(x - 4a)
= x^{4} - P_{1}x^{3} + P_{2}x^{2} - P_{3}x + P_{4}\\
\intertext{where}
P_{1} &= a + 2a + 3a + 4a = 10a,\\
P_{2} &= 1 \cdot 2a^{2} + 1 \cdot 3a^{2} + 1 \cdot 4a^{2} + 2 \cdot 4a^{2} + 3 \cdot 4a^{2} = 35a^{2},\\
P_{3} &= 2 \cdot 3 \cdot 4a^{3} + 1 \cdot 3 \cdot 4a^{2} + 1 \cdot 2 \cdot 4a^{3} + 1 \cdot 2 \cdot 3a^{3}= 50a^{3},\\
P_{4} &= 1 \cdot 2 \cdot 3 \cdot 4a^{4} = 24a^{4},
\intertext{so that}
\MoveEqLeft (x - a)(x - 2a)(x - 3a)(x - 4a)
= x^{4} - 10ax^{3} + 35a^{2}x^{2} - 50a^{3}x + 24a^{4}.
\end{align*}

\end{document}


• I honestly did not know the \MoveEqLeft-command, and also I seldom used the align-environment. Your set-up allowed me to understand how to use the align-environment coherently. Thank you very much, Bernard! Dec 10, 2014 at 3:41

Here is how I would do it:

\documentclass{article}

\usepackage{mathtools}

\begin{document}

\noindent We have
\begin{equation*}
(x - a)(x - 2a)(x - 3a)(x - 4a)
= x^{4} - P_{1}x^{3} + P_{2}x^{2} - P_{3}x + P_{4}
\end{equation*}
where
\begin{align*}
P_{1} &= a + 2a + 3a + 4a\\
&= 10a,\\
P_{2} &= 1 \cdot 2a^{2} + 1 \cdot 3a^{2} + 1 \cdot 4a^{2} + 2 \cdot 4a^{2} + 3 \cdot 4a^{2}\\
&= 35a^{2},\\
P_{3} &= 2 \cdot 3 \cdot 4a^{3} + 1 \cdot 3 \cdot 4a^{2} + 1 \cdot 2 \cdot 4a^{3} + 1 \cdot 2 \cdot 3a^{3}\\
&= 50a^{3},\\
P_{4} &= 1 \cdot 2 \cdot 3 \cdot 4a^{4}\\
&= 24a^{4},
\end{align*}
so that
\begin{equation*}
(x - a)(x - 2a)(x - 3a)(x - 4a)
= x^{4} - 10ax^{3} + 35a^{2}x^{2} - 50a^{3}x + 24a^{4}.
\end{equation*}

\end{document}


• Thank you very much for all the corrections you made. I could use the aforementioned set up for my work for it is more organised than the set up I had in mind. Dec 9, 2014 at 20:11